Multi-Slice Radiomic Analysis of Apparent Diffusion Coefficient Metrics Improves Evaluation of Brain Alterations in Neonates With Congenital Heart Diseases - Zhu, Meijiao; Zhao, Dadi; Wang, Ying; Zhou, Qinghua; Wang, Shujie; Mo, Xuming; Yang, Ming; Sun, Yu (Frontiers in Neurology, 2020)
Apparent diffusion coefficient (ADC) can provide phenotypic information of brain lesions, which can aid the diagnosis of brain alterations in neonates with congenital heart diseases (CHDs). However, the corresponding clinical significance of quantitative descriptors of brain tissue remains to be elucidated. By using ADC histograms and texture analysis, this study aimed to investigate the diagnostic value of single-slice and multi-slice measurements for assessing brain alterations in neonates with CHDs. ADC images were acquired from 60 neonates with echocardiographically confirmed non-cyanotic CHDs and 22 healthy controls (HCs) treated at Children’s Hospital of Nanjing Medical University from 2012 to 2016. Histogram metrics and texture features were extracted and correlated to the gestational age for both single and multiple slices of the whole brain. The diagnostic performance of ADC metrics for CHDs was evaluated by using analysis of covariance and receiver operating characteristic . For both the CHD and HC groups, ADC metrics were inversely correlated with the gestational age in single and multi-slice measurements (P<0.05). Histogram metrics were significant for identifying CHDs (P <0.05), while textural features were not. Multi-slice ADC values (P <0.01) exhibited greater diagnostic performance for CHDs than single-slice ADC values (P <0.05). Our findings indicate that radiomic analysis based on ADC maps can objectively provide more quantitative information regarding brain development in neonates with CHDs. ADC histogram metrics for the whole brain may be more clinically significant in identifying atypical brain development in these patients. Of note, our results suggest that multi-slice ADC can achieve greater diagnostic performance for CHD than single-slice.